Joint-interpretation of 2-D electrical resistivity method and borehole data for subsurface lithology identification - Bery, Andy Anderson; Nordiana, M. M.; Kiu, Y. C.; Nur Amalina, M. K. A.; Saidin, M.; Mohamamad-Afiq, A.; Nur-Amalina, A. M. (AIP Publishing, 2017)
There have been improvement in the subsurface investigation using non-destructive geophysical method. These were supported by improvement in data inversion method for 2-D resistivity imaging method. This geophysical method have been used for many environmental and engineering studies, such as slope monitoring, cavities detection, buried man-made structures and so on. This paper present the 2-D data inversion in electrical resistivity method which was carried out in Penang, Malaysia. This non-destructive method is used to image the subsurface for soil’s lithology purpose. In addition, two inline boreholes were used to validate and verify the obtained results of electrical resistivity imaging. Based on the electrical resistivity imaging, the subsurface is made up of four type of materials. They are sandy silt, silty sand, sand and lastly weathered granite. Sandy silt and silty sand soils give resistivity values of 65-220 Ωm and 120-770 Ωm. Meanwhile for sand and weathered granite materials, their resistivity values are 220-1400 Ωm and 410-2600 Ω.m respectively. Beside than electrical resistivity imaging, this work also present the distribution of conductivity for the investigated subsurface via the 2-D conductivity model. In conclusion, the used of the non-destructive geophysical method in this study is successful in image the investigated subsurface lithology and the investigation coverage area is enhanced instead of information from two discrete points of the geotechnical boreh oles. Therefore, the joint-interpretation of these two technical methods is capable and reliable to give information about the Earth’s subsurface lithology.